AlGaN nanowall network structure grown on sapphire (0001) substrate by laser molecular beam epitaxy. (January 2019) - Tyagi, Prashant; Ramesh, Ch.; Kushvaha, S.S.; Senthil Kumar, M.
Abstract: Self-assembled AlGaN nanowall networks have been grown heteroepitaxially on sapphire (0001) substrate using laser molecular beam epitaxy (LMBE) technique. The effect of growth temperature on the formation of AlGaN nanowall network structure has been studied in the range of 500–700 °C. It is found that the growth of AlGaN under strong N-rich flux condition at a high growth temperature of 700 °C is conducive for the formation of self-assembled nanowall network. In-situ reflection high energy electron diffraction exhibits the three-dimensional growth of the AlGaN nanowall network structure oriented along c-axis. The nanowall width and pore size are measured to be 10–40 and 30–70 nm, respectively, by using field emission scanning electron microscopy. From room temperature photoluminescence measurement, a strong ultra-violet (UV) emission at about 3.52 eV due to band-to-band transition is obtained for the AlGaN nanowall structure with a high UV-to-yellow luminescence intensity ratio indicating a good optical quality. The grown AlGaN nanowall network is suitable for the applications in field emitters, photo-detectors and other nitride-based optoelectronic devices.